Solar Cell Electric Bike In The Development Of Environmentally Transportation Technology - Malik Abdillah; Fauzan Azis Karo Karo; Fajar risqullah; Niko Franceda Silalahi; Solly Aryza (Sean Institute, 2024)
An Increasing carbon emissions from the transportation sector are one of the main issues in global climate change, so that environmentally friendly transportation solutions are needed. This study aims to develop an optimal design for an efficient and sustainable solar-powered electric bicycle. The methodology used includes experimental design, performance testing, and qualitative and quantitative data analysis on efficiency and technical and non-technical barriers. The results of the study show that the integration of monocrystalline solar panels, lithium-ion batteries, and DC electric motors with a smart controller system produces a design that can travel up to 60 km per full charge, with an energy consumption of 0.05 kWh/km. Compared to conventional electric bicycles, this bicycle has higher efficiency and faster charging times. However, there are several obstacles, such as the efficiency of solar panels which is affected by the weather and the high initial cost of technology, as well as non-technical challenges in the form of low public awareness and minimal government policy incentives. The conclusion of this study is that solar-powered electric bicycles have great potential as an environmentally friendly transportation solution in Indonesia. Technology development and cross-sector support are needed to optimize its implementation.